2004
DOI: 10.1111/j.1365-2249.2004.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mRNA for Th1 and Th2 cytokine-associated transcription factors and suppressors of cytokine signalling in peripheral blood mononuclear cells of patients with atopic dermatitis

Abstract: SUMMARYAtopic dermatitis is characterized by Th2-dominant immunity. Recently many intracellular molecules have been reported to regulate cytokine expression and T cell differentiation. GATA-3 and T-box expressed in T cells (T-bet) are transcription factors that play a critical role in the development of Th2 and Th1 immunity, respectively. Suppressor of cytokine signalling (SOCS)-3 and SOCS-5, are negative regulators of the cytokine signalling induced by IL-12 and IL-4, respectively. Txk is a transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
2
42
0
3
Order By: Relevance
“…Data from skin biopsies obtained from uninvolved skin of eczematous patients indicate that acute skin lesions contain significantly more cells producing IL-4, IL-5 and IL-13, but not IFN compared with chronic lesions [5]. In chronic lesions cells expressing IL-4 and IL-13 were significantly decreased, while cells expressing IL-5 and IFN were increased.…”
Section: Introductionmentioning
confidence: 96%
“…Data from skin biopsies obtained from uninvolved skin of eczematous patients indicate that acute skin lesions contain significantly more cells producing IL-4, IL-5 and IL-13, but not IFN compared with chronic lesions [5]. In chronic lesions cells expressing IL-4 and IL-13 were significantly decreased, while cells expressing IL-5 and IFN were increased.…”
Section: Introductionmentioning
confidence: 96%
“…AD is characterized by sino-pulmonary infections, dermatitis, cutaneous viral infections, altered eosinophil levels, elevated serum IgE, squamous cell carcinomas, and a high incidence of food allergies [12][13][14]. Aarkawa et al reported that different cytokines are present in the peripheral blood mononuclear cells of patients with atopic dermatitis [15]. Therefore, in this study, we investigated the prognostic value of eosinophil and related cytokines in atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Больные БА характеризуются повышением экспрессии STAT6 и активности IL-4 сигнализации. Выявленное нами повыше-ние экспрессии транскрипционного фактора GATA-3 при бронхиальной астме согласуется с данными литературы [5,9] о повышении его экспрессии при атопии и представляется вполне закономерным, поскольку, по данным некото-рых авторов [25,26], STAT6 может увеличивать экспрессию GATA-3. В этой связи представляют интерес выявленные нами положительные кор-реляционные связи между уровнем экспрессии STAT6 и GATA-3.…”
Section: Discussionunclassified
“…В частности, при исследовании мононуклеров периферической крови больных атопическим дерматитом [5] в отсутствие какой-либо стиму-ляции определялось существенное повышение уровней экспрессии GATA-3 и SOCS3 (супрес-сора цитокиновой сигнализации) в сравнении с практически здоровыми лицами.…”
Section: Discussionunclassified